Carbohydrate-Binding Module and Linker Allow Cold Adaptation and Salt Tolerance of Maltopentaose-Forming Amylase From Marine Bacterium Saccharophagus degradans 2-40T - Ding, Ning; Zhao, Boyang; Ban, Xiaofeng; Li, Caiming; Venkataram Prasad, B. V.; Gu, Zhengbiao; Li, Zhaofeng (Frontiers in Microbiology, 2021)
Marine extremophiles produce cold-adapted and/or salt-tolerant enzymes to survive in harsh conditions. These enzymes are naturally evolved with unique structural features that confer a high level of flexibility, solubility and substrate-binding ability compared to mesophilic and thermostable homologs. Here, we identified and characterized an amylase, SdG5A, from the marine bacterium Saccharophagus degradans 2-40T. We expressed the protein in Bacillus subtilis and found that the purified SdG5A enabled highly specific production of maltopentaose, an important health-promoting food and nutrition component. Notably, SdG5A exhibited outstanding cold adaptation and salt tolerance, retaining approximately 30% and 70% of its maximum activity at 4 °C and in 3M NaCl, respectively. It converted 68% and 83% of starch into maltooligosaccharides at 4 °C and 25 °C, respectively, within 24 hours, with 79% of the yield being the maltopentaose. By analyzing the structure of SdG5A, we found that the C-terminal carbohydrate-binding module (CBM) coupled with an extended linker, displayed a relatively high negative charge density and superior conformational flexibility compared to the whole protein and the catalytic domain. Consistent with our bioinformatics analysis, truncation of the linker-CBM region resulted in a significant loss in activities at low temperature and high salt concentration. This highlights the linker-CBM acting as the critical component for the protein to carry out its activity in biologically unfavorable condition. Together, our study indicated that these unique properties of SdG5A have great potential for both basic research and industrial applications in food, biology, and medical and pharmaceutical fields.